A Hierarchy Model of Income Distribution - Blair Fix (Forum on Capital As Power - Toward a New Cosmology of Capitalism, 2018)
Based on worldly experience, most people would agree that firms are hierarchically organized, and that pay tends to increase as one moves up the hierarchy. But how this hierarchical structure affects income distribution has not been widely studied. To remedy this situation, this paper presents a new model of income distribution that explores the effects of social hierarchy. This `hierarchy model' takes the limited available evidence on the structure of firm hierarchies and generalizes it to create a large-scale simulation of the hierarchical structure of the United States economy. Using this model, I conduct the first quantitative investigation of hierarchy's effect on income distribution. I find that hierarchy plays a dominant role in shaping the tail of US income distribution. The model suggests that hierarchy is responsible for generating the power-law scaling of top incomes. Moreover, I find that hierarchy can be used to unify the study of personal and functional income distribution, as well as to understand historical trends in income inequality.
Keywords: P16; 330; income distribution; hierarchy; power